Colorado water, June 2021 - Mokry, Melissa, editor; Colorado Water Center, publisher (Colorado State University. Libraries, 2021)
Newsletter of the Colorado Water Center. Theme: Climate change & adaptation.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water supply -- Colorado; Water use -- Colorado; Water supply -- Management -- Colorado